Asymmetric Membrane Capsules for Extended Delivery of the Weakly Basic Drug Carvedilol - Kumar Guarve; Ghanshyam Das Gupta (MDPI AG, 2010)
The objective of this study was to demonstrate that asymmetric membrane capsules can be used to deliver a poorly water soluble drug with a pH dependent solubility, such as carvedilol, for extended periods of time by modulating solubility with acid. In this study, the effect of the concentration of pH regulating agent and osmotic agents on the release rate of the active material was investigated. For this purpose, asymmetric membrane capsules of carvedilol were prepared using cellulose acetate as a semi-permeable membrane, containing glycerol as plasticizer, and fructose and fumaric acid were used as osmotic agent and pH regulating agent, respectively. In osmotic systems, the release rate of an excipient relative to the release rate of the drug is an important factor that determines the duration of drug release. Owing to high acidic strength and low aqueous solubility, fumaric acid resulted in simultaneous release and maintained a constant micro-environmental condition for the dissolution of the weakly basic drug. Finally, it was observed that the release rate of carvedilol was influenced by the concentration of fumaric acid and fructose. The optimal formulation was found to be able to deliver carvedilol at the rate of approximate zero-order up to 20 h, independent of release media and agitation rate.